2018
DOI: 10.21037/jgo.2018.01.17
|View full text |Cite
|
Sign up to set email alerts
|

Updates on immunotherapy for colorectal cancer

Abstract: Despite significant advances in standard of care therapies, the 5-year survival rate for metastatic colorectal cancer (CRC) remains around 12%. Immunotherapy has not provided the stellar advances in colorectal cancer that has been seen in other malignancies. Immunotherapy appears to play a pivotal role in microsatellite unstable CRC tumors where the response rates are profound. These results have led to FDA approval of pembrolizumab for MSI-H CRC tumors. Additional research into several new immune agents inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
117
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(118 citation statements)
references
References 80 publications
0
117
0
1
Order By: Relevance
“…In colon adenocarcinoma (COAD) and stomach adenocarcinoma (STAD), patients with high-MSI cancer (MSI-H) showed a significantly higher infiltration of antitumor and tumor helper cells, such as Tc, γδ T, NK, and DC ( Figure S6A), but a significantly lower infiltration of tumor suppressor cells (Tr1 and neutrophils) and CD8 naïve cells ( Figure S6b). These factors may partially explain the better outcomes of patients with MSI-H colorectal cancer undergoing immunotherapy [27] . Furthermore, we observed that some immune cell types showed stage-related profiles in cancers.…”
Section: Case Study Of Immucellai Application To Tcga Pan-cancer Datamentioning
confidence: 99%
“…In colon adenocarcinoma (COAD) and stomach adenocarcinoma (STAD), patients with high-MSI cancer (MSI-H) showed a significantly higher infiltration of antitumor and tumor helper cells, such as Tc, γδ T, NK, and DC ( Figure S6A), but a significantly lower infiltration of tumor suppressor cells (Tr1 and neutrophils) and CD8 naïve cells ( Figure S6b). These factors may partially explain the better outcomes of patients with MSI-H colorectal cancer undergoing immunotherapy [27] . Furthermore, we observed that some immune cell types showed stage-related profiles in cancers.…”
Section: Case Study Of Immucellai Application To Tcga Pan-cancer Datamentioning
confidence: 99%
“…Despite the significant advances of custom treatment method, the high migration and invasion capacity have been a bottle-neck for eliminating the mortality, which kept the 5-year survival rate of CRC under 12% [2][3][4]. In addition, several other factors were also identified to influence CRC prognosis, such as health-related quality of life [5], genome stability [6,7], aberrant gene expression [8,9], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, due to the inverse correlation between MSI and aneuploidy in CRC, our results suggest that this BCS value could be established as a cutoff to define the edge between low and high aneuploid tumors. In fact, while high aneuploid tumors show poor response to immunotherapy, it has been suggested that CMS1 microsatellite unstable tumors are likely to show a positive response to immune checkpoints inhibitors (Kalyan, Kircher, Shah, Mulcahy, & Benson, 2018;Le et al, 2015). However, BCS was not associated with overall survival in patients after relapse (data not shown).…”
Section: Discussionmentioning
confidence: 96%